The Relationship between Previous Tuberculosis Treatment and HIV Status with Multidrug-Resistant Tuberculosis (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Multidrug-resistant tuberculosis (MDR-TB) is becoming major public health issues in the world. Among the causes are history of previous TB treatment and increased co-infection of TB-HIV (Human Immunodeficiency Virus). This study aimed to identify the relationship between history of previous TB treatment and HIV status with MDR-TB. This is a case control study. The sample case was patients with MDR-TB, while sample control was patient who have drug-sensitive TB. Secondary data was obtained from patient medical records and laboratory results at Rotinsulu Pulmonary Hospital Bandung. Data were analyzed using chi-square. Multiple logistic regression was used to identify the dominant factor that influence the occurrence of MDR-TB. This study showed that the history of previous TB treatment was statistically significant with MDR-TB (p value= 0.001; OR= 18.889; 95% CI= 4.093-87.172) and it is the dominant factor that influence MDR-TB (p value= 0.0001; OR= 56.84; 95% CI= 6.9- 468.87). HIV infection at control group (who contracted drug-sensitive TB) was 26.1% (p value= 0.022). This finding suggested that HIV testing should be performed to each TB and MDR-TB patients and increased collaboration TB-HIV program between the other health care facilities should ensue. Drug sensitivity testing should be conducted at the start of TB treatment for patients with previous TB treatment and TB-HIV co-infection.